Evaluating the efficacy of the Family Check-Up Online: A school-based, eHealth model for the prevention of problem behavior during the middle school years. (December 2019) - Stormshak, Elizabeth A.; Seeley, John R.; Caruthers, Allison S.; Cardenas, Lucia; Moore, Kevin J.; Tyler, Milagra S.; Fleming, Christopher M.; Gau, Jeff; Danaher, Brian
Abstract: This study evaluated the efficacy of a family-centered preventive intervention, the Family Check-Up (FCU), delivered as an online, eHealth model to middle school families. To increase accessibility of family-centered prevention in schools, we adapted the evidence-based FCU to an online format, with the goal of providing a model of service delivery that is feasible, given limited staffing and resources in many schools. Building on prior research, we randomly assigned participants to waitlist control ( n = 105), FCU Online as a web-based intervention ( n = 109), and FCU Online with coaching support ( n = 108). We tested the effects of the intervention on multiple outcomes, including parental self-efficacy, child self-regulation, and child behavior, in this registered clinical trial (NCT03060291). Families engaged in the intervention at a high rate (72% completed the FCU assessment) and completed 3-month posttest assessments with good retention (94% retained). Random assignment to the FCU Online with coaching support was associated with reduced emotional problems for children ( p = .003, d = −0.32) and improved parental confidence and self-efficacy ( p = .018, d = 0.25) when compared with waitlist controls. Risk moderated effects: at-risk youth showed stronger effects than did those with minimal risk. The results have implications for online delivery of family-centered interventions in schools.